2014
DOI: 10.1556/aling.61.2014.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Degemination in Hungarian: Phonology or phonetics?

Abstract: It is traditionally held with respect to Hungarian degemination that geminates do not occur in this language word initially or flanked by another consonant on either side. The occurrence of geminates, true and fake ones alike, is said to be impossible except intervocalically or utterance finally (if preceded by a vowel and followed by a pause). However, this traditional view is oversimplified. Siptár (2000) proposed to amend it by positing three different degemination rules, applying at word level, postlexical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to the traditional view, it is assumed that geminates must surface as short if they are flanked by another consonant on either side, (this process is called degemination: Siptár and Gráczi 2014;Deme et al 2019). Recent findings showed that Present study (spontaneous speech)…”
Section: Gradients Ofmentioning
confidence: 99%
“…According to the traditional view, it is assumed that geminates must surface as short if they are flanked by another consonant on either side, (this process is called degemination: Siptár and Gráczi 2014;Deme et al 2019). Recent findings showed that Present study (spontaneous speech)…”
Section: Gradients Ofmentioning
confidence: 99%